Comparative Study Between Insertions of Postoperative Drain Versus No Drain After Total Thyroidectomy (Medical Forum Monthly, 2020)
Objective: To compare total thyroidectomy with insertion of post-operative drain versus no drain in terms of level of post-operative pain, duration of hospital stays and post-operative hematoma, seroma and wound infection.Study Design: Randomized controlled clinical trial study.Place and Duration of Study: This study was conducted at the Department of General Surgery, SKBZ/CMH, Muzaffarabad for 02 years from June 2018 to June 2020.Materials and Methods: After taking permission from hospital ethical committee, a total of 62 patients were included, who were undergoing total thyroidectomy for benign multinodular goiter admitted in Department of Surgery, SKBZ/CMH, Muzaffarabad.Results: Mean age of patients was 39.90 ± 14.13 years. Male patients were 54.8% while females were 45.2%. The score of pain and duration of hospital stay was statistically high in the drain group in comparison to the no drain group. After T-test and Chi-square test, there was no significant association found in both groups in terms of hospital stay or Post-operative pain regarding effect modifiers like age or gender.Conclusion: In post-operated cases of thyroid surgery where drains were not placed, were associated with short duration of hospital stay and less post-operative pain. So the results of this study do not support the regular insertion of drain after thyroid surgery.